Biochanin A protect against lipopolysaccharide-induced acute lung injury in mice by regulating TLR4/NF-κB and PPAR-γ pathway. (January 2020) - Hu, Xiansheng; Qin, Hongyu; Li, Yunpeng; Li, Jingxian; Fu, Lianjun; Li, Musen; Jiang, Cheng; Yun, Jinyan; Liu, Zhihu; Feng, Yao; Yao, Yuxuan; Yin, Baishuang
Abstract: Acute lung injury (ALI) is a serious respiratory syndrome featured with uncontrolled inflammatory response. Biochanin A has been showed to possess and anti-inflammatory effect. This study intended to explore the suppression of biochanin A on lipopolysaccharide (LPS)-induced ALI in mice. Seven hours later LPS-induced ALI model established, the indexes including, pathological changes, MPO activity, wet/dry ratio, proinflammatory cytokines TNF-α, IL-1β, and IL-6, production, as well as and TLR4/NF-κB and PPAR-γ signaling pathway expression were compared bwtween different groups. In addition, bronchoalveolar lavage fluid (BALF) was collected and the levels of total protein, inflammatory cells and TNF-α, IL-1β, and IL-6 were detected. The results revealed that LPS lead to significantly lung pathological injury, and damage of lung vascular permeability showing by higher lung wet/dry ratio and total protein levels in the BALF when compared to the control group mice. However, these changes significantly reversed by biochanin A. Moreover, the levels of inflammatory cells in BALF, proinflammatory cytokines TNF-α, IL-1β, and IL-6, in both lung and BALF were also dose-dependently reduced by biochanin A during ALI process. To investigate the anti-inflammatory mechanisms of biochanin A, we found that biochanin A significantly inhibited the activation of TLR4/NF-κB signaling pathway induced by LPS. Furthermore, the expression of PPAR-γ also markedly increased in the mice after treated with biochanin A. In conclusion, biochanin A alleviated LPS-induced ALI by inhibiting the inflammatory response, which was mediated via down-regulating the activation of TLR4/NF-κB signaling pathway and enhancing the expression of PPAR-γ. Highlights: Biochanin A significantly inhibited LPS-induced inflammatory response in the lung. Biochanin A significantly inhibited LPS-induced TLR4/NF-κB signaling pathway activation. Biochanin A significantly increased PPAR-γ expression in the lung.